The Role of the Family in Online Learning on Students' Motivation, Interest and Learning Achievement - Suryani Suryani (RIRAI Publisher, 2023)
This research was motivated by conditions of achievement and the need to learn during dare, the lack of support and motivation given by parents during dare learning made students bored and bored when completing the assignments given by the teacher. Families have differences in viewing education based on the principles they adhere to. The role of parents, apart from raising them, is also to educate and accompany children in any matter, one of which is in dare learning, in dare learning parents act as teachers, facilitators, motivators and directors. The aim of this research is to reveal children's learning conditions and interests, the role of the family as facilitator, motivator and director while studying from home. This type of research uses qualitative research, namely descriptive analysis, where this research uses research full of theory and expert analysis. The data analyzed are the results of interviews, observations and documents using photographic evidence. The data analysis stages carried out were data reduction, data presentation, conclusions and data verification. The subjects of this research were 8 informants, 6 main informants and 2 supporting informants. The results of the research show that the condition of learning achievement is influenced by children's interest in learning, and the role of parents is based on the principles adopted by each family, parents do not fully play a direct role in guiding children in bold learning, as long as bold learning achievement is carried out by teachers and parents work together to determine the abilities and development of students' learning achievements, and based on the grades obtained by students, they are not in accordance with their supposed abilities, where children's learning achievements depend on the role of parents in them, so the role of parents who have ethnic differences greatly influences interest and children's learning achievements in determining children's learning success in learning that is carried out boldly.